Induction of Mkp-1 and Nuclear Translocation of Nrf2 by Limonoids from Khaya grandifoliola C.DC Protect L-02 Hepatocytes against Acetaminophen-Induced Hepatotoxicity - Kouam, Arnaud F.; Yuan, Fei; Njayou, Frédéric N.; He, Hongtao; Tsayem, Roméo F.; Oladejo, Babayemi O.; Song, Fuhang; Moundipa, Paul F.; Gao, George F. (Frontiers in Pharmacology, 2017)
Drug-induced liver injury (DILI) is a major clinical problem where natural compounds hold promise for its abrogation. Khaya grandifoliola (Meliaceae) is used in Cameroonian traditional medicine for the treatment of liver related diseases and has been studied for its hepatoprotective properties. Till date, reports showing the hepatoprotective molecular mechanism of the plant are lacking. The aim of this study was therefore to identify compounds from the plant bearing hepatoprotective activity and the related molecular mechanism by assessing their effects against acetaminophen (APAP)-induced hepatotoxicity in normal human liver L-02 cells line. The cells were exposed to APAP (10mM) or co-treated with phytochemical compounds (40 μM) over a period of 36h and, biochemical and molecular parameters assessed. Three known limonoids namely 17-epi-methyl-6-hydroxylangolensate, 7-deacetoxy-7-oxogedunin and deacetoxy-7R-hydroxygedunin were identified. The results of cells viability and membrane integrity, reactive oxygen species generation and lipid membrane peroxidation assays, cellular glutathione content determination as well as expression of cytochrome P450 2E1 demonstrated the protective action of the limonoids. Immunoblotting analysis revealed that limonoids inhibited APAP-induced c-Jun N-terminal Kinase phosphorylation (p-JNK), mitochondrial translocation of p-JNK and Bcl2-associated X Protein, and the release of Apoptosis-inducing Factor into the cytosol. Interestingly, limonoids increased the expression of Mitogen-activated Protein Kinase Phosphatase (Mkp)-1, an endogenous inhibitor of JNK phosphorylation and, induced the nuclear translocation of Nuclear Factor Erythroid 2-related Factor-2 (Nrf2) and decreased the expression of Kelch-like ECH-associated Protein-1. The limonoids also reversed the APAP-induced decreased mRNA levels of Catalase, Superoxide Dismutase-1, Glutathione-S-Transferase and Methionine Adenosyltransferase-1A. The obtained results suggest that the isolated limonoids protect L-02 hepatocytes against APAP-induced hepatotoxicity mainly through increase expression of Mkp-1 and nuclear translocation of Nrf2. Thus, these compounds are in part responsible of the hepatoprotective activity of K. grandifoliola and further analysis including in vivo and toxicological studies are needed to select the most potent compound that may be useful as therapeutic agents against DILI.